The impact of European and Asian immigration of the XIX—early XXI centuries on the development of Brazil and the challenge of integrating immigrants in Brazilian society - A. A. Musyka (Ибероамериканские тетради)
The European and Asian immigration influenced greatly the development of Brazil. Moreover, in the 19th and early 20th centuries it was one of the key factors of Brazilian growth as far as it helped to preserve the integrity of Brazilian territory and contributed to the development of its plantation economy. Throughout the history of Brazil the immigration process has been controlled by the Brazilian